Reference librarians and institutional repositories - Rockman, Ilene F. (Reference services review, 2005)
This e-book is focused on the role of the reference librarian in the development, management, dissemination, and sustainability of institutional repositories (IRs). We know that reference librarians are essential to the teaching, learning, and research processes on their campuses. Now, comes another new role for them as libraries move forward to establish and populate new forms of digital publishing to capture and maintain campus-based intellectual assets, assist with scholarly communication and preservation efforts, and enhance the prestige of their institutions.